Low dielectric adhesive with self-repairing function and preparation method and application thereof
By using a low-dielectric adhesive prepared by special epoxy resin and epoxy polysulfide glue, and through the combination of fluorine-containing anhydride curing agent and organic strong alkali promoter, the problems of high dielectric constant and dielectric loss in multi-layer FPC are solved, and the self-healing function of the adhesive is realized, improving the reliability and service life of the FPC.
Patent Information
- Application Number
- CN202310063797.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-01-17
AI Technical Summary
The prior art is difficult to reduce the dielectric constant and dielectric loss in the production of multi-layer FPCs. At the same time, the dielectric layer is prone to micro-damage in the process, affecting the reliability and service life of the FPC.
A low-dielectric adhesive with self-healing function is prepared by using special epoxy resins and epoxy polysulfide glues. Through the combination of fluorine-containing anhydride curing agent and organic strong alkali promoter, the dielectric properties of the adhesive are reduced through anionic polymerization and curing reaction, and the adhesive is given a self-healing function in the disulfide bond exchange reaction.
It significantly reduces the dielectric constant and dielectric loss of the adhesive, improves the processability, reliability and service life of multi-layer FPCs, and makes the product lighter and thinner and has higher integration.
Smart Images

Figure CN116355565B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a low-dielectric adhesive with a self-repairing function and a low-loss flexible adhesive-coated copper foil prepared therefrom. Background Art
[0002] The advent of the 5G communication era has brought about earth-shaking changes in the way people live and work, and signal transmission is rapidly developing in the direction of high frequency and high speed. Flexible printed circuits (FPCs) have excellent characteristics such as light weight, thin thickness, and free bending and folding. They are the core components of electronic devices. The higher the frequency and speed of signal transmission, the greater the signal loss. The dielectric properties of the dielectric layer that plays an insulating role are one of the key factors in signal loss. Therefore, how to reduce the dielectric constant and dielectric loss of the dielectric material has become the key to preparing low-loss 5G materials.
[0003] In addition, as the integration of electronic components becomes higher and higher, the size becomes smaller and smaller, and the performance becomes more and more powerful, FPC is also required to develop in the direction of miniaturization, multi-layering, lightweight and high density. The raw material for producing FPC, flexible copper-clad laminate, is composed of copper foil and dielectric layer. The dielectric layer is polyimide or polyethylene terephthalate film. When preparing multi-layer FPC, additional adhesive film is needed to bond the copper-clad laminate. Therefore, the dielectric layer includes adhesive film in addition to polyimide or polyethylene terephthalate film. Therefore, the traditional multi-layer FPC is thick and does not meet the development requirements of small, light and thin.
[0004] In the production of multi-layer high-density FPC, processes such as through-hole production and punching are required, which can easily cause micro-damage to the dielectric layer, seriously affecting the reliability and service life of the multi-layer FPC.
[0005] Therefore, it is necessary to develop an adhesive material with lower dielectric constant, dielectric loss and self-healing function. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the present invention provides a low-dielectric adhesive with self-repairing function and an adhesive-coated copper foil prepared therefrom.
[0007] The technical objectives of the present invention are achieved through the following technical solutions:
[0008] The invention provides a low dielectric adhesive with a self-repairing function, and the formula of the low dielectric adhesive comprises the following raw material components by weight: 50-150 parts of special epoxy resin, 25-300 parts of epoxy polysulfide glue, 50-385 parts of fluorine-containing anhydride curing agent, 0.2-1.0 parts of accelerator, and 350-2500 parts of solvent.
[0009] Furthermore, the special epoxy resin of the present invention is aromatic and does not contain hydroxyl groups.
[0010] Furthermore, the special epoxy resin of the present invention is selected from one or a mixture of two or more of trifunctional epoxy resin, condensed ring naphthalene epoxy resin, o-cresol epoxy resin, phenol formaldehyde epoxy resin and biphenyl phenol epoxy resin.
[0011] Furthermore, the trifunctional epoxy resin of the present invention has an epoxy equivalent of 163-173 and a molecular structure of Or the epoxy equivalent of the condensed ring naphthalene epoxy resin is 207-221, and the molecular structure is Or the epoxy equivalent of the o-cresol epoxy resin is 198-210, and the molecular structure is
[0012] Or the phenol formaldehyde epoxy resin has an epoxy equivalent of 180-200 and a molecular structure of Or the epoxy equivalent of the biphenyl phenol type epoxy resin is 280-310, and the molecular structure is
[0013]
[0014] Furthermore, the epoxy polysulfide adhesive of the present invention is an aliphatic epoxy-modified polysulfide adhesive and / or an aromatic epoxy-modified polysulfide adhesive.
[0015] Furthermore, the aliphatic epoxy modified polysulfide rubber of the present invention has an epoxy equivalent of 500-600 and a molecular structure of
[0016] Formula VI; or the aromatic epoxy modified polysulfide rubber having an epoxy equivalent of 280-350 molecular structure is
[0017]
[0018] Furthermore, the fluorine-containing acid anhydride curing agent of the present invention is selected from one or a mixture of two or more of tetrafluorosuccinic anhydride, hexafluoroglutaric anhydride, tetrafluorophthalic anhydride and 4,4-hexafluoroisopropylphthalic anhydride.
[0019] Furthermore, the promoter of the present invention is an organic strong base; preferably, the promoter is selected from 4-dimethylaminopyridine and / or 1,8-diazabicyclo[5.4.0]undec-7-ene; preferably, the solvent is selected from one or a mixture of two or more of dioxane, N,N-dimethylformamide and cyclohexanone.
[0020] Another technical object of the present invention is to provide a method for preparing a low dielectric adhesive with self-repairing function, comprising the following steps:
[0021] S1. Weigh each raw material component according to the formula described in claim 1;
[0022] S2. Heat and dissolve the special epoxy resin, epoxy polysulfide adhesive, fluorine-containing acid anhydride curing agent and solvent, cool to room temperature, add accelerator and stir well to obtain.
[0023] Another technical object of the present invention is to provide a method for preparing a coated copper foil, comprising the following steps: uniformly coating the low dielectric adhesive with self-repairing function as described in any one of claims 1 to 8 on the copper foil, adjusting the thickness of the coated adhesive, controlling the thickness of the adhesive layer to 15 μm, and drying.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The adhesive prepared by the present invention, since the special epoxy resin and epoxy polysulfide adhesive used do not contain high polar groups such as hydroxyl groups, and fluorine-containing acid anhydride is used as a curing agent, an anionic polymerization curing reaction is performed under the catalysis of a promoter, thereby avoiding the introduction of active hydrogen and introducing a large amount of fluorine atoms into the adhesive, thereby greatly reducing the dielectric properties of the adhesive.
[0026] 2. The epoxy polysulfide adhesive used in the present invention contains a large number of disulfide bonds, and under the catalysis of the promoter being an organic strong base, the disulfide bonds can undergo an exchange reaction, thereby giving the adhesive material a self-repairing function. When used as a multi-layer FPC dielectric layer, the processability, reliability and service life of the multi-layer FPC can be improved.
[0027] 3. The present invention prepares a flexible coated copper foil by coating a low dielectric adhesive with self-healing function on the rolled copper foil, which can replace the traditional copper clad laminate for making multi-layer FPC. Since the use of build-up film is avoided, the product is lighter, thinner and more integrated. In addition, the adhesive material has a lower dielectric constant and dielectric loss, so the loss in the high-frequency and high-speed signal transmission process can be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1a Schematic diagram of lamination and pressing of samples for peeling force testing according to the present invention.
[0029] Figure 1b It is a schematic diagram of the peeling method during the peeling force test of the present invention. DETAILED DESCRIPTION
[0030] In order to better illustrate the technical purpose, technical scheme and advantages of the present invention, the present invention is further described in conjunction with the accompanying drawings and specific embodiments. The sources of the raw material components in the embodiments of the present invention and the comparative examples are all commercially available products if not mentioned. The trifunctional epoxy resin TPNE5501 (epoxy equivalent 163-173), condensed ring naphthalene epoxy resin NPTE4000 (epoxy equivalent 207-221), o-cresol epoxy resin EOCN6000 (epoxy equivalent 198-210), phenol formaldehyde epoxy resin PFNE7400 (epoxy equivalent 180-20) and biphenyl phenol type epoxy resin BPNE3501 (epoxy equivalent 280-310) used in the present invention are all purchased from Hunan Jiashengde Material Technology Co., Ltd. Aliphatic epoxy modified polysulfide rubber EPS-25 (epoxy equivalent 500-600) and aromatic epoxy modified polysulfide rubber EPS-70 (epoxy equivalent 280-350) were purchased from Akzo Nobel of the Netherlands. Rolled copper foil was purchased from Nippon Mining and Metals Co., Ltd. of Japan, model BHYX-92F-HA, thickness 12 μm. The unit of weight parts mentioned in the examples is gram.
[0031] 1. Preparation of low-dielectric adhesive and low-loss flexible coated copper foil with self-healing function
[0032] Example 1
[0033] 1. Preparation of low dielectric adhesive with self-healing function
[0034] Add 50 parts of trifunctional epoxy resin TPNE5501, 25 parts of aliphatic epoxy modified polysulfide glue EPS-25, 60 parts of tetrafluorosuccinic anhydride, and 400 parts of dioxane into a three-necked bottle, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 0.2 parts of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0035] 2. Preparation of low-loss flexible coated copper foil
[0036] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0037] Example 2
[0038] 1. Preparation of low dielectric adhesive with self-healing function
[0039] Add 50 parts of fused-ring naphthalene epoxy resin NPTE4000, 25 parts of aromatic epoxy modified polysulfide glue EPS-70, 70 parts of hexafluoroglutaric anhydride, and 450 parts of N,N-dimethylformamide into a three-necked flask, heat to 60-80°C and continue to stir magnetically. After fully dissolved, cool to room temperature, continue to add 0.2 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0040] 2. Preparation of low-loss flexible coated copper foil
[0041] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0042] Example 3
[0043] 1. Preparation of low dielectric adhesive with self-healing function
[0044] Add 50 parts of o-cresol epoxy resin EOCN6000, 50 parts of aromatic epoxy modified polysulfide glue EPS-70, 90 parts of tetrafluorophthalic anhydride, and 550 parts of cyclohexanone into a three-necked bottle, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 0.3 parts of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0045] 2. Preparation of low-loss flexible coated copper foil
[0046] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0047] Example 4
[0048] 1. Preparation of low dielectric adhesive with self-healing function
[0049] Add 50 parts of phenol formaldehyde epoxy resin PFNE7400, 50 parts of aliphatic epoxy modified polysulfide glue EPS-25, 80 parts of hexafluoroisopropyl phthalic anhydride, and 550 parts of cyclohexanone into a three-necked flask, heat to 60-80°C and continue magnetic stirring. After fully dissolved, cool to room temperature, continue to add 0.3 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0050] 2. Preparation of low-loss flexible coated copper foil
[0051] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0052] Example 5
[0053] 1. Preparation of low dielectric adhesive with self-healing function
[0054] Add 50 parts of biphenyl phenol type epoxy resin BPNE3501, 25 parts of aliphatic epoxy modified polysulfide glue EPS-25, 50 parts of hexafluoroisopropyl phthalic anhydride, and 350 parts of N,N-dimethylformamide into a three-necked bottle, heat to 60-80°C and continue to stir magnetically, cool to room temperature after fully dissolved, continue to add 0.2 parts of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0055] 2. Preparation of low-loss flexible coated copper foil
[0056] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0057] Example 6
[0058] 1. Preparation of low dielectric adhesive with self-healing function
[0059] Add 100 parts of biphenyl phenol type epoxy resin BPNE3501, 50 parts of aromatic epoxy modified polysulfide glue EPS-70, 110 parts of tetrafluorophthalic anhydride, and 800 parts of dioxane into a three-necked flask, heat to 60-80°C and continue to stir magnetically, cool to room temperature after fully dissolved, continue to add 0.5 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0060] 2. Preparation of low-loss flexible coated copper foil
[0061] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0062] Example 7
[0063] 1. Preparation of low dielectric adhesive with self-healing function
[0064] Add 100 parts of phenol formaldehyde epoxy resin PFNE7400, 50 parts of aliphatic epoxy modified polysulfide glue EPS-25, 135 parts of hexafluoroglutaric anhydride, and 850 parts of dioxane into a three-necked bottle, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 0.5 parts of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0065] 2. Preparation of low-loss flexible coated copper foil
[0066] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0067] Example 8
[0068] 1. Preparation of low dielectric adhesive with self-healing function
[0069] Add 100 parts of o-cresol epoxy resin EOCN6000, 100 parts of aromatic epoxy modified polysulfide glue EPS-70, 140 parts of tetrafluorosuccinic anhydride, and 1000 parts of N,N-dimethylformamide into a three-necked flask, heat to 60-80°C and continue magnetic stirring, cool to room temperature after full dissolution, continue to add 0.5 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0070] 2. Preparation of low-loss flexible coated copper foil
[0071] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0072] Example 9
[0073] 1. Preparation of low dielectric adhesive with self-healing function
[0074] Add 100 parts of fused-ring naphthalene epoxy resin NPTE4000, 150 parts of aliphatic epoxy modified polysulfide glue EPS-25, 125 parts of tetrafluorosuccinic anhydride, and 1150 parts of cyclohexanone into a three-necked flask, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 0.5 parts of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0075] 2. Preparation of low-loss flexible coated copper foil
[0076] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0077] Example 10
[0078] 1. Preparation of low dielectric adhesive with self-healing function
[0079] Add 100 parts of trifunctional epoxy resin TPNE5501, 150 parts of aromatic epoxy modified polysulfide glue EPS-70, 240 parts of hexafluoroglutaric anhydride, and 1450 parts of cyclohexanone into a three-necked flask, heat to 60-80°C and continue magnetic stirring. After fully dissolved, cool to room temperature, continue to add 0.7 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0080] 2. Preparation of low-loss flexible coated copper foil
[0081] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0082] Embodiment 11
[0083] 1. Preparation of low dielectric adhesive with self-healing function
[0084] Add 150 parts of trifunctional epoxy resin TPNE5501, 200 parts of aliphatic epoxy modified polysulfide glue EPS-25, 275 parts of tetrafluorophthalic anhydride, and 1900 parts of N,N-dimethylformamide into a three-necked bottle, heat to 60-80°C and continue magnetic stirring. After fully dissolved, cool to room temperature, continue to add 1 part of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0085] 2. Preparation of low-loss flexible coated copper foil
[0086] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0087] Example 12
[0088] 1. Preparation of low dielectric adhesive with self-healing function
[0089] Add 150 parts of fused-ring naphthalene epoxy resin NPTE4000, 200 parts of aromatic epoxy modified polysulfide glue EPS-70, 300 parts of hexafluoroisopropylphthalic anhydride, and 1950 parts of dioxane into a three-necked flask, heat to 60-80°C and continue to stir magnetically. After fully dissolved, cool to room temperature, continue to add 1 part of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0090] 2. Preparation of low-loss flexible coated copper foil
[0091] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0092] Example 13
[0093] 1. Preparation of low dielectric adhesive with self-healing function
[0094] Add 150 parts of o-cresol epoxy resin EOCN6000, 300 parts of aliphatic epoxy modified polysulfide glue EPS-25, 285 parts of hexafluoroisopropyl phthalic anhydride, and 2200 parts of dioxane into a three-necked bottle, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 1 part of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0095] 2. Preparation of low-loss flexible coated copper foil
[0096] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0097] Embodiment 14
[0098] 1. Preparation of low dielectric adhesive with self-healing function
[0099] Add 150 parts of phenol formaldehyde epoxy resin PFNE7400, 300 parts of aromatic epoxy modified polysulfide glue EPS-70, 385 parts of tetrafluorophthalic anhydride, and 2500 parts of N,N-dimethylformamide into a three-necked flask, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 1 part of 1,8-diazabicyclo[5.4.0]undec-7-ene, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0100] 2. Preparation of low-loss flexible coated copper foil
[0101] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0102] Embodiment 15
[0103] 1. Preparation of low dielectric adhesive with self-healing function
[0104] Add 150 parts of biphenyl phenol type epoxy resin BPNE3501, 300 parts of aliphatic epoxy modified polysulfide glue EPS-25, 235 parts of hexafluoroglutaric anhydride, and 2050 parts of cyclohexanone into a three-necked bottle, heat to 60-80°C and continue magnetic stirring, cool to room temperature after fully dissolved, continue to add 1 part of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a low dielectric adhesive with self-healing function.
[0105] 2. Preparation of low-loss flexible coated copper foil
[0106] The prepared low dielectric adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90°C for 0.4-0.6 h for drying to obtain a low-loss flexible adhesive-coated copper foil.
[0107] Comparative Example 1
[0108] 1. Preparation of traditional adhesives
[0109] Add 100 parts of epoxy resin EPON828, 88 parts of methylhexahydrophthalic anhydride, and 600 parts of N,N-dimethylformamide into a three-necked bottle, heat to 60-80°C and continue magnetic stirring. After fully dissolved, cool to room temperature, continue to add 0.3 parts of 4-dimethylaminopyridine, and stir for 1-2 minutes to obtain a traditional adhesive.
[0110] 2. Preparation of flexible coated copper foil
[0111] The above-mentioned traditional adhesive is evenly coated on the rolled copper foil, and the thickness of the adhesive layer is controlled to be 15 μm by adjusting the thickness of the coated adhesive. The foil is placed in an oven at 70-90° C. for 0.4-0.6 h for drying to obtain a flexible adhesive-coated copper foil.
[0112] 2. Performance Test
[0113] 1. Test methods
[0114] (1) Self-repair efficiency test method
[0115] Place two low-loss flexible glue-coated copper foils with their glued surfaces facing each other, and embed a polytetrafluoroethylene film with a width of 80 mm at the front end, which should be longer than the glue-coated copper foil. Figure 1a Then put it into the flat vulcanizer, set the temperature to 200℃, the pressure to 2MPa, keep it warm for 2h to fully cure and bond, cool it down to room temperature and take out the sample. Cut the sample into 200×25mm 2 The strips were tested for peeling force using a universal tensile testing machine (Shenzhen Xinsansi Company, model: SANS CMT 6000), with the tensile speed set to 5 mm / min. Figure 1b As shown, the peeling force F0 is obtained.
[0116] Put the low-loss flexible glue-coated copper foil into the flat vulcanizer separately, set the temperature to 200℃ and the pressure to 2MPa, keep it warm for 2h to fully cure, cool it down to room temperature and take out the sample. Then, place the two cured glue-coated copper foils opposite to each other, and embed a polytetrafluoroethylene film with a width of 80mm. Figure 1a As shown, the plate vulcanizer is put into the plate vulcanizer again and pressed according to the same pressing parameters to allow the cured adhesive layers to fully self-repair. The self-repaired sample is subjected to the same peeling force test to obtain the peeling force F1 after self-repair. Self-repairing efficiency η = F1 / F0*100%.
[0117] (2) Test of dielectric constant and dielectric loss
[0118] The low-loss flexible adhesive-coated copper foil was placed in a flat-plate vulcanizer, set at 200°C and 2MPa, kept warm for 2 hours for full curing, cooled to room temperature and removed. The copper foil was then removed by etching to obtain a cured film, and the dielectric constant and dielectric loss of the film were measured at a frequency of 10 GHz using a KEYSIGHT N5224B vector network analyzer from the United States.
[0119] 2. Test results
[0120] Table 1. Test results of self-repair efficiency, dielectric constant and dielectric loss of Examples 1-15 and Comparative Example 1
[0121]
[0122]
[0123] Traditional adhesives mostly use bisphenol A or bisphenol F type epoxy resins, and use compounds containing active hydrogen groups such as amino, carboxyl, and hydroxyl as curing agents. Since the epoxy resin itself contains a large number of hydroxyl groups, and a large number of hydroxyl groups are also introduced after the curing reaction of the curing agent, the traditional adhesive has a higher dielectric constant and dielectric loss, as shown in Comparative Example 1 in Table 1, resulting in high-frequency and high-speed signal transmission. During, a higher loss occurs. In addition, in the production process of multilayer FPC, it is necessary to go through processes such as drilling blind holes and punching, causing inevitable micro-damage or micro-cracks, and the traditional adhesive, after being fully cured, does not have the function of micro-damage repair because it will not form new chemical bonds, thereby seriously affecting the reliability and service life of the multilayer FPC product. The adhesive prepared by the present invention, because the special epoxy resin and epoxy polysulfide used do not contain high polar groups such as hydroxyl groups, and fluorine-containing acid anhydride is used as a curing agent, anionic polymerization curing reaction is carried out under the catalysis of a promoter, while avoiding the introduction of active hydrogen, a large number of fluorine atoms are introduced into the adhesive, thereby greatly reducing the dielectric constant and dielectric loss of the adhesive. In addition, the special epoxy resin belongs to the aromatic family and contains a large number of rigid groups, so that the adhesive material has good mechanical strength and heat resistance.
[0124] The epoxy polysulfide adhesive used in the present invention contains a large number of disulfide bonds, and the organic strong base 4-dimethylaminopyridine and 1,8-diazabicyclo[5.4.0]undec-7-ene are selected as promoters, which can be used as promoters for the curing reaction between epoxy resin and curing agent on the one hand, and can catalyze the exchange reaction of disulfide bonds in the epoxy polysulfide adhesive on the other hand. When the dielectric layer is micro-damaged due to processing, the disulfide bonds in the epoxy polysulfide adhesive can undergo an exchange reaction on the crack section, and the re-established disulfide bonds between the sections are bonded and repaired to the microcracks. Therefore, the addition of epoxy polysulfide adhesive gives the adhesive material a self-repairing function, thereby improving the processability, reliability and service life of the multi-layer FPC. As shown in Table 1, compared with Comparative Example 1 (self-repair efficiency is 0), Examples 1-15 all show that the cured adhesive still has a certain bonding ability (i.e., the self-repair efficiency is ≥ 27%), which means that when microcracks appear, multiple heat treatments are required in the subsequent multi-layer FPC production process, such as SMT. The microcrack interface can be bonded to achieve the self-repair function, and no additional repair treatment process is required. It can be seen that the introduction of the self-repair function can improve the processability, reliability and service life of the multi-layer FPC to a certain extent. In addition, epoxy polysulfide glue has good toughness, so the prepared adhesive also has good toughness.
[0125] As electronic products develop towards high integration, miniaturization and high performance, FPCs must be miniaturized, multi-layered, lightweight and high-density. Traditional multi-layer FPCs are made by laminating copper-clad laminates and build-up adhesive layers. In addition to the polyimide or polyethylene terephthalate film of the copper-clad laminate itself as a dielectric layer, there is an additional adhesive layer, which has a high thickness and weight and does not meet the requirements of being light and thin. The present invention directly coats a low-dielectric adhesive with a self-healing function on the rolled copper foil to prepare a flexible coated copper foil, which can replace traditional copper-clad laminates for making multi-layer FPCs. Since the use of build-up adhesive films is avoided, the product is lighter, thinner and more integrated.
[0126] It can be seen that the multilayer FPC made by using the low-loss flexible coated copper foil prepared by the present invention as raw material has many advantages such as low loss, high reliability, long service life, lightness and thinness.
[0127] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. In addition, the present invention may also be implemented in other ways. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present invention may be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A low dielectric adhesive with self-repairing function, characterized in that: The formula comprises the following raw material components by weight: 50-150 parts of special epoxy resin, 25-300 parts of epoxy polysulfide glue, 50-385 parts of fluorine-containing anhydride curing agent, 0.2-1.0 parts of accelerator, and 350-2500 parts of solvent; the special epoxy resin is aromatic and does not contain hydroxyl groups; the special epoxy resin is selected from one or a mixture of two or more of trifunctional epoxy resin, condensed ring naphthalene epoxy resin, o-cresol epoxy resin, phenol formaldehyde epoxy resin and biphenyl phenol epoxy resin; the accelerator is an organic strong base selected from 4-dimethylaminopyridine and / or 1,8-diazabicyclo[5.4.0]undec-7-ene; the epoxy polysulfide glue is aliphatic epoxy modified polysulfide glue and / or aromatic epoxy modified polysulfide glue; the epoxy equivalent of the aliphatic epoxy modified polysulfide glue is 500-600, and the molecular structure is Or the aromatic epoxy modified polysulfide rubber has an epoxy equivalent of 280-350 and a molecular structure of 2. The low dielectric adhesive with self-repairing function according to claim 1, characterized in that: The epoxy equivalent of the trifunctional epoxy resin is 163-173, and the molecular structure is Or the epoxy equivalent of the condensed ring naphthalene epoxy resin is 207-221, and the molecular structure is Or the epoxy equivalent of the o-cresol epoxy resin is 198-210, and the molecular structure is Or the phenol formaldehyde epoxy resin has an epoxy equivalent of 180-200 and a molecular structure of Or the epoxy equivalent of the biphenyl phenol type epoxy resin is 280-310, and the molecular structure is 3. The low dielectric adhesive with self-repairing function according to claim 1, characterized in that: The fluorine-containing acid anhydride curing agent is selected from one or a mixture of two or more of tetrafluorosuccinic anhydride, hexafluoroglutaric anhydride, tetrafluorophthalic anhydride and 4,4-hexafluoroisopropylphthalic anhydride.
4. The low dielectric adhesive with self-repairing function according to claim 1, characterized in that: The solvent is selected from one of dioxane, N,N-dimethylformamide, and cyclohexanone, or a mixture of two or more thereof.
5. A method for preparing a low dielectric adhesive with self-repairing function, characterized in that: The following steps are involved: S1. Weigh each raw material component according to the formula described in claim 1; S2. Heat and dissolve the special epoxy resin, epoxy polysulfide adhesive, fluorine-containing acid anhydride curing agent and solvent, cool to room temperature, add accelerator and stir well to obtain.
6. A method for preparing a glue-coated copper foil, characterized in that: The following steps are involved: The low dielectric adhesive with self-repairing function as claimed in any one of claims 1 to 4 is uniformly coated on the copper foil, the thickness of the coated adhesive is adjusted to control the thickness of the adhesive layer to be 15 μm, and then dried.
Citation Information
Patent Citations
Orthopedic apparatus
EP0101081A1
Epoxy resin composition for build-up insulating film, insulating film formed therefrom, and multilayer printed circuit board having the same
CN103540102A
Polysulfide sealant with room-temperature self-repairability and high elongation percentage
CN106753192A